KNOWLEDGE OF TRIMESTER III PRIMIGRAVIDA PREGNANT WOMEN IN FACING CHILDBIRTH AT THE BATU AJI COMMUNITY HEALTH CENTER - Zaini Kadhafi Saragih; Roni Aldiano (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2020)
Background :The low level of public awareness about the health of pregnant women is a determining factor in the mortality rate, although there are still many factors that must be considered in dealing with this problem. The issue of death that occurs is due to common indications, namely bleeding, pregnancy poisoning accompanied by convulsions, abortion, and infection (Depkes RI, 2015). The purpose of this study was to determine the knowledge of third trimester Primigravida pregnant women in dealing with childbirth at Batu Aji Health Center. Method :The design of this study was descriptive. The research was carried out at Puskesmas Batu Aji. The population in this study were all trimester III primigravida pregnant women who visited and conducted ANC examinations at Batu Aji Health Center as many as 40 pregnant women. The sampling technique used in this study was total sampling. Univariate analysis aims to explain or describe the characteristics of each research variable. The form of univariate analysis depends on the type of data. For numerical data, mean or average, median and standard deviation is used. Result : The results and conclusions of this study were the knowledge of third trimester primigravida pregnant women at Batu Aji Community Health Center was 35 (87.5%) mothers with good knowledge, 5 (12.5%) mothers experienced less knowledge. Congclusions : Knowledge of third trimester primigravida pregnant women at Batu Aji Community Health Center is 35 (87.5%) mothers with good knowledge, 5 (12.5%) mothers experience less knowledge